The effect of imagery in the tennis service precision and performance - Sergio Gregorio da Silva; Wagner de Campos; Cosme Franklim Buzzachera; Heriberto Colombo; Kleverton Krinski; Hassan Mohamed Elsangedy; Suzane de Oliveira; Ricardo Weigert Coelho (Universidade Federal de Santa Catarina, 2008)
The purpose of this study was to determine whether an imagery training intervention program could affect the performance of junior Brazilian tennis players in two distinct situations: (1) serving without precision and (2) serving at a target with precision. The study used a quasi-experimental design with pretest-posttest and a control group. Data we recollected from a sample of 46 junior male tennis players with ages ranging from 14 to 16 years old (mean 15.06 ± 0.83), all formally registered with the state tennis federation of Paraná, Brazil. The subjects were divided into two groups: (G1) Technical practice only, used as a control group (n=24); (G2) Imagery group, given imagery training as well as technical practice (n=22). The data were analyzed using analysis of variance (2x2x2) for repetitive measures to p< 0.05. The results demonstrated an effect (p< 0.05) between experimental and control groups in the situation "service without precision". However, the difference in the situation of "service with precision" was not significant (p> 0.5). These results demonstrate the effectiveness of imagery training for building self confidence to improve performance, but only in the situation that did not require motor precision. It can be concluded that, imagery is a reliable method for improving service performance in tennis and should be used in a specific manner for specific situations, primarily those which require more improvement in performance-related factors. Resumo Este estudo objetivou investigar como uma intervenção com treinamento mental (imaginação) afetaria o desempenho de jogadores de tênis juniores brasileiros em duas situações distintas do saque no tênis de campo: (1) saque sem precisão e (2) saque com precisão. A investigação seguiu delineamento quase-experimental com pré e pós-teste e grupo controle. Os dados foram coletados de uma amostragem de 46 sujeitos, jogadores de tênis de campo, do sexo masculino, com idade entre 14 a 16 anos e média de 15,06 ± 0, 83 anos, registrados na Federação Paranaense de Tênis. Os sujeitos foram divididos em dois grupos: Grupo controle (G1), 22 sujeitos que participaram apenas do treinamento de aprimoramento da técnica do saque e Grupo Experimental (G2), composto por 24 sujeitos, os quais participaram do treinamento da técnica e aplicação da intervenção da imaginação. Para analisar os dados foi usada uma ANOVA fatorial para medidas repetidas (2x2x2), P<0,05. Os resultados demonstraram melhora do grupo experimental no desempenho do saque na situação saque sem precisão, após a intervenção da imaginação. Já, a situação de precisão o resultado não foi significativo, demonstrando a efetividade da intervenção com treinamento mental (imaginação) na autoconfiança somente na situação que não requereu ação com precisão motora. Conclui-se que, a imaginação é um método eficiente para melhoria do desempenho no saque do tênis de campo, e deve ser aplicada de maneira especifica para cada situação, principalmente aquela com maior demanda de fatores a serem considerados no desempenho.